Associations between sexual satisfaction and function and the severity of lower urinary tract symptoms among men in a rural sub-Saharan African community - Macnab, Andrew John (Can Urol Assoc J, 2019)
INTRODUCTION: The recognized association between erectile dysfunction (ED) and lower urinary tract symptoms (LUTS) from high-income countries is unreported from Africa. Authentic figures on prevalence of ED and LUTS from Africa are scarce in the literature. This study was conducted to quantify sexual function and satisfaction among Ugandan men in relation to LUTS severity. METHODS: A convenience sample of men participating in a parallel, cross-sectional survey was used. The population, men >55 years living in Sheema district, Uganda, were recruited into two cohorts: those living in the community and those seeking clinic care due to bother from LUTS. This was to ensure inclusion of a full spectrum of LUTS. The instruments were the International Prostate Symptom Score (IPSS) to quantify LUTS and the Epstein Inventory (EI) to assess four measures of sexual functioning. Bivariate analysis compared community and clinic cohort participants, LUTS severity, and each sexual functioning item with two-sample t-tests for means and Chi-square tests of independence for categorical versions. RESULTS: Participants included 415 men (238 community and 177 clinic) at mean age of 67.5 years vs. 62.9 (p<0.001) with mean IPSS of 9.32 vs. 17.07 (p≤0.001). Lower mean satisfaction with sexual activity and frequency of erections occurred in the clinic cohort (p≤0.001). Overall, all four questions assessing dissatisfaction with sexual function were significantly correlated with worsening LUTS; sexual satisfaction and frequency of sexual drive were also influenced by age and low levels of education. CONCLUSIONS: These are the first data describing the severity relationship between LUTS and ED in African men. Respondents reported dissatisfaction in the past year with the level of their sexual activity, frequency of sexual drive, ability to have erections, and sexual performance that related statistically to the severity of their LUTS.